Early-Holocene temperature variability inferred from chironomid assemblages at Hawes Water, northwest England - Lang, B; Bedford, A; Brooks, SJ; Jones, RT; Richardson, N; Birks, HJB; Marshall, JD (SAGE PUBLICATIONS LTD, 2010)
This paper presents the first high-resolution chironomid-inferred mean July air temperature (C-IT) reconstruction for the early Holocene from England. The reconstruction is based on a core recovered from a terrestrialised carbonate bench at Hawes Water, a small hard-water lake in northwest England. The record shows that temperatures rose rapidly after the Younger Dryas with temperatures reaching 14.0 degrees C at the beginning of the Holocene. Over millennial timescales, the temperature record points to a slight rise in temperatures towards the top of the sequence at around 8000 years before the year 2000 (b2k). The trend is punctuated by a series of cool oscillations (at 11 200, 11 400, 10 700, 10 400, 9300 and 8300 b2k) and by a short period (11 300 to 10 250 b2k) when temperatures were considerably warmer (up to 14.9 degrees C). The five cool oscillations coincide with temperature reversals found elsewhere in the North Atlantic region and in the Greenland ice core records. These cool events correlate well with both meltwater fluxes from the Laurentide and Scandinavian ice sheets and periods of low solar activity. Two of these oscillations (at 9300 and 8300 b2k) vary significantly from the early-Holocene mean. C-IT shift rapidly during both these events and temperatures fall similar to 1.6 degrees C below the early-Holocene mean trend for similar to 50-60 years. The results presented here provide an insight into the instability of the early-Holocene climate in the British Isles and demonstrate the sensitivity of chironomids to rapid climatic events during the early Holocene.